2009
DOI: 10.2165/00002512-200926060-00003
|View full text |Cite
|
Sign up to set email alerts
|

Constipation in the Elderly

Abstract: Constipation is a highly prevalent and bothersome disorder that negatively affects patients' social and professional lives and places a great economic burden on both patients and national health services. An accurate determination of the prevalence of constipation is difficult because of the various definitions used, but many epidemiological studies have shown that it affects up to 20% of the population at any one time. Although constipation is not a physiological consequence of normal aging, decreased mobilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
49
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 35 publications
1
49
0
Order By: Relevance
“…Commonly used pharmacological agents for the treatment of constipation include bulk-forming laxatives (ispaghula husk, methylcellulose, and bran), stimulant laxatives (senna, bisacodyl, sodium picosulfate, and glycerin suppositories), osmotic laxatives (lactulose, magnesium sulphate, and phosphate enema), fecal softeners (docusate sodium, liquid paraffin, and arachis oil), and prokinetic agents (prucalopride and tegaserod) [1, 6]. However, laxatives also may induce side effects, such as severe diarrhea [7].…”
Section: Introductionmentioning
confidence: 99%
“…Commonly used pharmacological agents for the treatment of constipation include bulk-forming laxatives (ispaghula husk, methylcellulose, and bran), stimulant laxatives (senna, bisacodyl, sodium picosulfate, and glycerin suppositories), osmotic laxatives (lactulose, magnesium sulphate, and phosphate enema), fecal softeners (docusate sodium, liquid paraffin, and arachis oil), and prokinetic agents (prucalopride and tegaserod) [1, 6]. However, laxatives also may induce side effects, such as severe diarrhea [7].…”
Section: Introductionmentioning
confidence: 99%
“…In the elderly, with chronic constipation, history and physical examination to exclude medication-induced constipation and secondary causes are the first step. [78]…”
Section: Introductionmentioning
confidence: 99%
“…Constipation is a highly prevalent and bothersome disorder that negatively affects patients' social and professional lives and places a great economic burden on both patients and national services (Spinzi et al, 2009). Many epidemiological studies have showed that it affects up to 20% of population, especially in the elderly, worldwide (Crowell et al, 2007;Pohl et al, 2008;Spinzi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Many epidemiological studies have showed that it affects up to 20% of population, especially in the elderly, worldwide (Crowell et al, 2007;Pohl et al, 2008;Spinzi et al, 2009). Investigations have demonstrated that if people only have a bowel movement every 3-4 days, they are more at risk for having colonic cancer, hemorrhoids, irritable bowel syndrome (IBS), and many other illnesses (Shimotoyodome et al, 2000;Yang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation